A divergent and metal free synthesis of sulfoximine tethered imidazoles, imidazopyridines, imidazothiazoles, imidazobenzothiazines, thiazoles and selenazoles12. Issue 17 (13th April 2017) - Battula, S. R. K.; Rama Kishore Putta, V. P.; Subbareddy, G. V.; Chakravarthy, I. E.; Saravanan, V.
Abstract : A divergent and metal free approach has been successfully developed for the synthesis of sulfoximine tethered heterocycles from a α-bromoalkanone building block. Abstract : A divergent and metal free approach has been successfully developed for the synthesis of sulfoximine tethered heterocycles. A key α-bromoalkanone intermediate3b has been reported for the first time. Various sulfoximine tethered imidazoles, imidazopyridines, thiozoloimidazoles, imidazobenzothiazines, thiazoles and selenazoles are made from this common sulfoximine building block.